LINGUISTIC AND EXTRALINGUISTIC FACTORS OF PERLOCUSIA - Z.L. Madumarova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
in this article, the linguistic and extralinguistic factors of perlocusia are covered in detail on the basis of taxa that rely on scientific theories.